PENYULUHAN PROGRAM POKOK TANAM TOGA MAHASISWA KKN-PPM UNIVERSITAS PGRI ADI BUANA SURABAYA DI DESA BULANG PRAMBON SIDOARJO - Erlin Ladyawati (Jurnal Abadimas Adi Buana, 2017)
Toga is an important thing to be aplication. Toga is a plant that has particularly many functions or can be meant by multi-purpose plants that can be applied in a household or community. Garden utilize unused for planting toga is a useful thing to do. TOGA (Plant Medicine Family) is a good thing to do, especially to improve the quality of health of people who use it as a plant gardener plants medicine family. Utilizing the plant medicine family of a good thing at the same time benefit from simple things become things much beneficial for conservationists or growers plant medicine family. Finally, many familys growed plant medicine family in the his house with many fariety plant medicine family, example jahe plant, kencur plant, onion plant, garlic plant and etc. So, we as a big family KKN-PPM University PGRI Adi Buana feels appriciate to people in the Bulang-Prambon.